Permodelan Pengekangan Kolom Pada Beton Mutu Normal Dengan Metode Elemen Hingga 3-D - Ridho Saleh Silaban; Darmansyah Tjitradi; Syahril Taufik (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The column is a critical element in the building structure, the failure of the column will directly result in the collapse of other related structural components. The column must have strength, stability and ductility. In increasing the capacity and ductility of the column by providing confinement, to protect concrete elements from breaking due to the influence of the working pressure. Analyzing ultimate axial load capability, stress-strain distribution patterns and crack patterns in concrete elements and column ductility. Tests of several models and variations of the restraint distance in short columns of normal concrete quality with longitudinal reinforcement of steel steels and carbon steel transversal reinforcement. The columns were analyzed using the Finite Element Analysis (FEA) method with the help of a full scale ANSYS 3-D application, with material properties for concrete using SOLID65 and steel reinforcement using LINK8 and SOLID45 loading plates. The type of pedestal used is the joints with axial loading (axial loadstep) centric direction. The effect of the restraint model and the variation of the restraint distance to the value of the column ultimate axial load for the whole model is relatively small with a ratio of 1.079, while for the ratio of the axial deformation ratio of 1.496. The pattern of stress and strain distribution when yielding spreads throughout the column area but when it reaches the ultimate distribution the concentration is concentrated in the support area. The first dominant crack occurs in the pedestal area and generally occurs in the concrete blanket layer, in the ultimate condition cracks have occurred evenly throughout the column area. The ratio of the ratio of ductility values ​​for all column models and the restraint distance is relatively large with a ratio value of 1.523